Parts of the day and their contextual implications in the Holy Qur’an - Hanani, Zaher Mohammad (Journal of Humanities & Social Sciences, 2021)
This research deals with (The Day divisions and their linguistic connotations in The Holy Qur’an). At the introduction the researcher showed the research significance   and its general elements. Next, a preface with the title (Before the start) showed the dimensions of this research, its origins and its intrinsic motives. Then, it presented night and day in terms of their concept, essence and origin. After that showed the sections of the day mentioned in the Holy Quran, which are seventeen sections, some of which overlap and group into one section; making it difficult to distinguish   between them, indicating their individual linguistic connotations and importance of to the human being.
Keywords: today; sections of the day; contextual semantics; the Holy Quran